Accelerated Oxidation Test of Freeze-Dried Pseudomonas Fluorescens BTP1, BB2 and PI9 Strains - Jean-Noel, Mputu Kanyinda; Tshimenga, Karl; Philippe, Noki (The Asia Journal of Applied Microbiology, 2015)
Pseudomonas fluorescens strains are very susceptible to damage during freeze-drying and storage. It would be useful to have longer lasting viable powders. Membrane oxidation is one of the factors responsible for damages suffered by P. fluorescens strains during storage. Singlet oxygen (1O2) is a highly reactive form of molecular oxygen that may harm living systems by oxidizing critical cellular macromolecules. We exposed freeze-dried powders of three strains P. fluorescens (BB2, BTP1 and PI9) to singlet oxygen produced by photosensitisation of Methylene Blue/ light during 2 hours. We observe a significant loss in survival rate, a pronounced oxidation of polyunsaturated fatty acids, protein oxidation (carbonyl groups) and protein insolubilisation. This study enables better predictions of types of packaging suitable for freeze-dried powders of P. fluorescens.